OPEN SPACE STANDARDS AND ITS RELATION TO CLIMATE CHANGE - Azrar Hadi (Jurnal Kajian Pengembangan Perkotaan, 2012)
Scientists agree that the activities of the mankind is the main cause of the increasing trend of the carbon dioxide and other greenhouse gases effects in the atmosphere. This continuing trend contributes to increase the global temperature at the extreme level and hence triggering melting glacier and creating uncertainties in the global ecosystem. The Panel on Climate Change (IPCC) reported that the burning of fossil fuels, deforestation and other human activities catalyze global warming faster than ever predicted before. This study investigates whether there is a close link between urban space eco-policy standard and the urban land use management and building regulations with climate change. The study shows that the building regulations are mainly intended to be instruments to address socio-economic and urban architectural issues instead of instruments to mitigate climate change.